Universal, low-cost, articulating support for smartphone use for magnification of structures in human dissection (Research, Society and Development, 2025)
Dissection of anatomical specimens is a necessary activity for preparing classes – and, consequently, for studying – the subject of Human Anatomy. Traditional dissection methods have proven valuable throughout history as efficient ways of producing cadaveric specimens with organized and didactic content, allowing students access to the most important structures of the human body. However, such methods do not always guarantee the preservation of smaller tissues, and it is common to lose some elements during the preparation of the specimens, which ends up depriving students of certain nuances of the practical study of the content. An alternative to this problem is the use of magnification structures, such as stereoscopes. However, the cost of these devices is quite expensive, especially if we consider the financial reality of educational and research institutions in Brazil. In this sense, this article seeks to demonstrate the feasibility of using smartphone cameras used on articulated steel supports as a cheap, practical and useful alternative for viewing minimal structures during the cadaveric dissection process, aiming at better preparation of anatomical specimens. Throughout the study, it was possible to observe the usefulness of this tool in preserving a greater number of cadaveric structures, allowing greater detail in the pieces produced and, consequently, more possibilities for the teaching-learning process carried out in the Human Anatomy discipline.